1998
DOI: 10.1177/039139889802101118
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Factor and Tissue Factor Pathway Inhibitor in Hemodialysis Patients

Abstract: Tissue factor and tissue factor pathway inhibitor are important in extrinsic coagulation. We investigated their clinical significance in hemodialysis patients. We took blood samples, prior to initiation of routine hemodialysis, from 73 patients on hemodialysis (35 men and 38 women aged 56.1+/-11.7 years on dialysis for 82.1+/-61.0 months), and determined tissue factor and tissue factor pathway inhibitor levels by ELISA. In the patients the tissue factor level was 704.5+/-141.6 pg/ml and the tissue factor pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…Soejima et al [35] proposed that not only an increase in the plasma levels of TF but also an increase in free TFPI posed the risk of a grim fate for patients with unstable Zemanová /Opatrný Jr/ Opatrná/Vít/Šefrna/Racek angina. In their study, Yorioka et al [36] observed that the TFPI levels in hemodialysis patients with occlusion of vascular access were higher than in patients without occlusion. To be able to propose other hypotheses beyond endothelial injury, plasma TF and TFPI activity measurements are needed.…”
Section: Discussionmentioning
confidence: 89%
“…Soejima et al [35] proposed that not only an increase in the plasma levels of TF but also an increase in free TFPI posed the risk of a grim fate for patients with unstable Zemanová /Opatrný Jr/ Opatrná/Vít/Šefrna/Racek angina. In their study, Yorioka et al [36] observed that the TFPI levels in hemodialysis patients with occlusion of vascular access were higher than in patients without occlusion. To be able to propose other hypotheses beyond endothelial injury, plasma TF and TFPI activity measurements are needed.…”
Section: Discussionmentioning
confidence: 89%
“…described higher levels of tissue factor on monocytes in hemodialysis patients in comparison to healthy controls [14]. Al-Saady et al showed a hypercoagulable state in patients with chronic renal failure as a contributing factor for the increased cardiovascular and cerebrovascular event rate [16].…”
Section: Discussionmentioning
confidence: 99%
“…They are known to modulate both inflammation and thrombosis, which promote the development of clinical atherosclerosis [13]. Tissue factor expression on monocytes is important in extrinsic coagulation and elevated in HD patients compared to healthy controls [14].…”
Section: Introductionmentioning
confidence: 99%
“…One important finding is that the presence of cardiovascular disease is closely linked to the tissue factor system [19]. Yorioka et al described higher levels of tissue factor on monocytes in haemodialysis patients in comparison to a healthy control group [14]. Pawlak et al demonstrated a relationship between increased oxidative stress and elevated tissue factor in peritoneal dialysis patients [20].…”
Section: Discussionmentioning
confidence: 99%
“…Binding of CD40L to its CD40 receptor on endothelial cell membranes induces an enhanced release of potent proinflammatory and atherosclerosis-promoting cytokines and chemokines (e.g., IL-6 and MCP-1) [13]. Tissue factor expression on monocytes is important in extrinsic coagulation and elevated in HD patients compared to that in healthy controls [14]. It is known that a disturbed platelet function is an important cause for thromboembolic and haemorrhagic complications in ESRD patients.…”
Section: Introductionmentioning
confidence: 99%